1991
DOI: 10.1002/etc.5620100204
|View full text |Cite
|
Sign up to set email alerts
|

An aquatic environmental safety assessment of linear alkylbenzene

Abstract: Linear alkylbenzene (LAB), the parent material from which the detergent surfactant linear alkylbenzene sulfonate (LAS) is manufactured, has the potential to enter the environment from several sources. Solubility, vapor pressure and soil partition measurements indicate that LAB would be distributed in air or adsorbed to soil or sediment. The material does not accumulate to significant levels in fish (BCF = 35) or undergo chemical or photochemical degradation in screening studies. LAB is readily biodegradable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 26 publications
0
35
1
Order By: Relevance
“…At present, a realistic environmental fate assessment of TAMs in the aquatic environment is precluded due to the lack of knowledge of key physico-chemical properties. Although similar behavior to TAMs has been reported for the photooxidation of LABs [38], they still show a preferential depletion of the internal substituted isomers in either in vitro cultures [35] or in environmental samples [16,18,23,25]. The ratio of internal to external isomers has indeed proposed as a degradation index [36].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…At present, a realistic environmental fate assessment of TAMs in the aquatic environment is precluded due to the lack of knowledge of key physico-chemical properties. Although similar behavior to TAMs has been reported for the photooxidation of LABs [38], they still show a preferential depletion of the internal substituted isomers in either in vitro cultures [35] or in environmental samples [16,18,23,25]. The ratio of internal to external isomers has indeed proposed as a degradation index [36].…”
Section: Resultsmentioning
confidence: 78%
“…The ratio of internal to external isomers has indeed proposed as a degradation index [36]. Gledhill et al [38] have applied a multimedia fugacity model to evaluate the fate of LABs in the environment and found that the atmospheric compartment is by far the most favored at equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…LABs consist of isomers with different phenyl substitutional positions. External isomers (i.e., isomers whose phenyl substitutional positions are near the terminal end of the alkyl chain) are preferentially biodegraded as compared to internal isomers (Bayona et al 1986;Takada and Ishiwatari 1990;Gledhill et al 1991;Gustafsson et al 2001). To quantitatively express the isomer composition, a ratio of internal to external isomers (i.e.…”
Section: Linear Alkylbenzenes and Sewage Inputmentioning
confidence: 99%
“…The existing database is spotty, at best (e.g. 41), and this limits the use of numerical modeling to predict the transport and fate of these compounds (86,87). Another important consideration is the nature of phase associations established during synthesis/production and how these affect exchange between solid and aqueous phases (e.g.…”
Section: Future Directions and Research Needsmentioning
confidence: 99%